Faktor- Faktor yang Berhubungan dengan Keaktifan Kader Posyandudi Wilayah Kerja Puskesmas Sonraen Kecamatan Amarasi SelatanTahun 2025 - Jurnia Nggai; Rina Waty Sirait; Dominirsep O. Dodo; Masrida Sinaga (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Posyandu cadre activity is a crucial factor in supporting the success of maternal and child health services at the community level. However, the level of cadre activity varies and is influenced by various factors. This study aims to determine the factors associated with Posyandu cadre activity in the working area of the Sonraen Community Health Center. This study used a quantitative design with a cross-sectional approach, conducted from November to December 2025. The population in this study was all 135 Posyandu cadres spread across 27 Posyandus, with a sample of 53 respondents selected using simple random sampling. Data were collected using a questionnaire and analyzed univariately and bivariately using chi-square tests. The results showed that the majority of cadres were active (67.9%). Cadres with good knowledge (71.7%), good motivation (67.9%), good support from health workers (71.7%), and good community support (73.6%). The chi-square test results showed a significant relationship between knowledge (p=0.003), motivation (p=0.000), support from health workers (p=0.002), and community support (p=0.001) and Posyandu cadre activity. The conclusion of this study is that there is a significant relationship between knowledge, motivation, support from health workers, and community support and Posyandu cadre activity in the Sonraen Community Health Center (Puskesmas). It is recommended that the Puskesmas improve guidance and training, and strengthen cross-sectoral support to increase cadre activity.